2011
DOI: 10.2174/1874325001105010115
|View full text |Cite
|
Sign up to set email alerts
|

Total Elbow Arthroplasty

Abstract: Total elbow arthroplasty has continued to evolve over time. Elbow implants may be linked or unlinked. Unlinked implants are attractive for patients with relatively well preserved bone stock and ligaments, but many favor linked implants, since they prevent instability and allow replacement for a wider spectrum of indications. Inflammatory arthropathies such as rheumatoid arthritis represent the classic indication for elbow arthroplasty. Indications have been expanded to include posttraumatic osteoarthritis, acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
63
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 40 publications
(46 reference statements)
1
63
0
1
Order By: Relevance
“…Aseptic loosening is one of the most common causes for revision of TEA (Fevang et al 2009;Skyttä et al 2009;Sanchez-Sotelo 2011). Aseptic loosening of total joint replacements often occurs due to osteolysis at boneimplant interfaces induced by ultra high molecular weight polyethylene (UHMWPE) wear debris (Revell et al 1978;Peters et al 1992;Cadambi et al 1994;Schmalzried et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Aseptic loosening is one of the most common causes for revision of TEA (Fevang et al 2009;Skyttä et al 2009;Sanchez-Sotelo 2011). Aseptic loosening of total joint replacements often occurs due to osteolysis at boneimplant interfaces induced by ultra high molecular weight polyethylene (UHMWPE) wear debris (Revell et al 1978;Peters et al 1992;Cadambi et al 1994;Schmalzried et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Levy et al reported a higher rate of revision for unlinked compared to linked implants. [18] Depending on the rigidity of the fixation of the humeral component to the ulnar component, the implant arthroplasties are designated as constrained, semiconstrained, and unconstrained [19]. In general, the constrained prostheses rarely are used because of their tendency to loosen and break.…”
Section: Discussionmentioning
confidence: 99%
“…The semiconstrained hinged prostheses have built-in valgus and varus laxity to provide for dissipation of forces. The GSB III, HSS-Osteonics, and the Coonrad-Morrey prostheses are semiconstrained [19].…”
Section: Discussionmentioning
confidence: 99%
“…Primary TEA used to be a salvage procedure only for low-demand patients but is increasingly being used for other indications including fractures, osteoarthritis and instability [7,8]. TEA is technically demanding [9] and regardless of design, reports on primary TEA have stated an overall fiveyear failure rate between eight and ten percent and approximately 15 % after ten years [10,11].…”
Section: Introductionmentioning
confidence: 99%